ANALISA DRUG RELATED PROBLEM PADA ENDOMETRIOSIS DI PUSKESMAS DUREN SERIBU PERIODE 1 JANUARI - 30 JUNI 2025 - Mustika Sari, Rahayu; Ambarsari, Niati (Journal of Pharmacy Tiara Bunda, 2025)
This study analyzed the incidence of drug-related problems, including adverse events and medical errors, and possible associated risk factors, in patients with endometriosis who used combined oral contraceptives (COCs) and progestins. Reports were collected between January 1, 2024, and June 30, 2025, regarding endometriosis patients in the Medical Record System at the Duren Seribu Community Health Center, Depok City. A disproportionate analysis was performed using the Gamma–Poisson Shrinker model to detect overreported drug–event pairs. Logistic regression analysis was used to explore potential risk factors. There were 23 reports regarding long-term hormonal treatment and 45 reports regarding other medications used for endometriosis. Long-term hormonal treatment included: 15 reports (22.0%) of combined oral contraceptives (COCs), 10 reports (14.7%) of oral progestins, 8 reports (11.76%) of injectable (depot) progestins, 23 reports (33.82%) of progestin-releasing IUDs, and 12 reports (17.64%) of progestin-only implants. Both combined oral contraceptives (COCs) and progestin-only products are relatively safe for patients with endometriosis. Combination therapy (polytherapy) has been negatively associated with several medical errors in COC users, while patients aged ≥30 years have had more pulmonary embolism cases but fewer reported product-related problems.